Deciphering ferroptosis in critical care: mechanisms, consequences, and therapeutic opportunities - Tan, Ruimin; Ge, Chen; Yan, Yating; Guo, He; Han, Xumin; Zhu, Qiong; Du, Quansheng (Frontiers in Immunology, 2024)
Ischemia-reperfusion injuries (IRI) across various organs and tissues, along with sepsis, significantly contribute to the progression of critical illnesses. These conditions disrupt the balance of inflammatory mediators and signaling pathways, resulting in impaired physiological functions in human tissues and organs. Ferroptosis, a distinct form of programmed cell death, plays a pivotal role in regulating tissue damage and modulating inflammatory responses, thereby influencing the onset and progression of severe illnesses. Recent studies highlight that pharmacological agents targeting ferroptosis-related proteins can effectively mitigate oxidative stress caused by IRI in multiple organs, alleviating associated symptoms. This manuscript delves into the mechanisms and signaling pathways underlying ferroptosis, its role in critical illnesses, and its therapeutic potential in mitigating disease progression. We aim to offer a novel perspective for advancing clinical treatments for critical illnesses.